Presenteeism and musculoskeletal symptoms among nursing professionals - Heloisa Ehmke Cardoso dos Santos; Maria Helena Palucci Marziale; Vanda Elisa Andres Felli (Universidade de São Paulo, 2018)
ABSTRACT Objective: to identify the prevalence of musculoskeletal symptoms in two stages (before and after six months of the first stage) and its association with presenteeism among nursing professionals. Method: longitudinal study with quantitative data conducted in a Brazilian teaching hospital with 211 nursing professionals. The instruments used for data collection were: Cultural and Psychosocial Influences on Disability - CUPID Questionnaire, used to identify the musculoskeletal symptoms and the Stanford Presenteeism Scale, used to verify presenteeism. The instruments were validated for Brazilian Portuguese. The study was approved by the Human Research Ethics Committee. Descriptive statistics, Mann Whitney test and regression analysis were used to analyze the data. Results: 158 (74.9%) professionals experienced presenteeism and 151 (71.6%) reported low back pain as musculoskeletal symptom. Professionals with low back pain had lower scores on the presenteeism scale and shoulder pain was related to loss of concentration during work. Conclusion: presenteeism lead to a reduction in work performance and was manifested in the presence of musculoskeletal symptoms. In addition, shoulder pain caused loss of concentration at work.